A STUDY ON THE THIRD YEAR ENGLISH DEPARTMENT STUDENTS’ ABILITY IN IDENTIFYING ROUND AND FLAT CHARACTERS OF READING SHORT DRAMA SCRIPTS, AT RIAU UNIVERSITY - Mustika, Afifah Zulfa; ', Afrianto; K, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed at investigating the level of the students’ ability at English Study Program of FKIP of University of Riau in identifying round and flat characters in reading short drama scripts and it what factors contributing to the ability of the students. The research design is a descriptive quantitative and qualitative research (mixed-method). There were 25 students chosen as the samples of this research. The instruments of the research were 30 multiple choice questions assesed by using Heaton’s formula that were analyzed by using Harris’ measurement. Then, interview questions were analyzed by using Gay (2000) ways. The quantitative data show that there were no students who were in excellent ability level, 5 students (25%) who were in good ability level. Then, there were 15 students (50%) who were in mediocre level and 5 students (25%) who were in very poor level. The qualitative data show that there are some factors which contributed to the students’ ability in identifying round and flat characters. They are related to students’ reading strategy (the beginning and the ending of the story), vocabulary mastery, guessing strategy and the length of the storyKey words: student, ability, round, flat, characters